2021
DOI: 10.1002/aic.17299
|View full text |Cite
|
Sign up to set email alerts
|

Conventional anddata‐drivenmodeling of filtered drag, heat transfer, and reaction rate ingas–particleflows

Abstract: This study presents conventional and artificial neural network‐based data‐driven modeling (DDM) methods to model simultaneously the filtered mesoscale drag, heat transfer and reaction rate in gas–particle flows. The dataset used for developing the DDM is filtered from highly resolved simulations closed by our recently formulated microscopic drag and heat transfer coefficients (HTCs). Results reveal that the filtered drag correction is nearly independent of filter size when including the filtered gas phase pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 51 publications
(94 reference statements)
0
28
0
Order By: Relevance
“…However, the relative importance and relevance between the newly introduced variables and the old variables may need to be identified. This is because the filtered drag correction is nearly independent of filter size when introducing the closure marker of the gas phase pressure gradient in traditional physics-based modeling . Moreover, whether the trained model can be well extrapolated to different gas–solid flow patterns is also an important issue in NN modeling .…”
Section: Current Status and Challengesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the relative importance and relevance between the newly introduced variables and the old variables may need to be identified. This is because the filtered drag correction is nearly independent of filter size when introducing the closure marker of the gas phase pressure gradient in traditional physics-based modeling . Moreover, whether the trained model can be well extrapolated to different gas–solid flow patterns is also an important issue in NN modeling .…”
Section: Current Status and Challengesmentioning
confidence: 99%
“…However, the data source of this study is generated by simulations of a relatively small domain in which there are possible numerical artifacts since the clusters or bubbles can grow to the domain scale and hence lead to unrealistic settlement velocity. Their later study further found that the correction model can still perform well by using the closure marker of the fluid phase pressure gradient in the absence of filter size . Except for the use of simulations to generate data sets, theoretical methods such as the energy minimization multiscale (EMMS) can also provide data for training.…”
Section: Current Status and Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…By filtering CFD–DEM data, Lei et al 29 proposed a heat transfer model as a function of the filtered solid volume fraction, the filter size and the dimensionless temperature difference between the two phases. Zhu et al 30 proposed a similar model with dimensional temperature difference. Lei et al 31 then extended the model by Zhu et al into the bidisperse systems.…”
Section: Introductionmentioning
confidence: 99%